Spatial Agglomeration, Technology and Outsourcing of Knowledge Intensive Business Services Empirical Insights from Italy - Roberto Antonietti; Giulio Cainelli (Fondazione Eni Enrico Mattei (FEEM), 2007)
Aim of this paper is to explore the main drivers of outsourcing of knowledge intensive business services by Italian manufacturing firms. While anecdotal and empirical evidence has emphasized labour cost and scale economies as behind firms choices to outsource production or service activities, here we focus on spatial agglomeration and technology as important factors. Using microeconomic data on a repeated cross-section of Italian manufacturing firms for the period 1998-2003, we develop a two-stage model in order to avoid selection bias: first, we estimate the determinants of the firm's decision to outsource business-related services; second, we estimate the main factors underlying the intensity and complexity of KIBS outsourcing, expressed by the number of service activities that are externalized. Our results show that labour cost-savings are not relevant in driving the decision to outsource KIBS, but ICT, R&D and location within a dense and technologically developed industrial district have very positive effects.
Keywords: L24; L84; R32; R12; 330; KIBS; Service Outsourcing; R&D; ICT; Spatial Agglomeration; Unternehmensdienstleistung; Outsourcing; Agglomerationseffekt; Forschung; Informationstechnik; Italien